2015
DOI: 10.1038/aps.2015.31
|View full text |Cite
|
Sign up to set email alerts
|

The edaravone and 3-n-butylphthalide ring-opening derivative 10b effectively attenuates cerebral ischemia injury in rats

Abstract: Oral administration of compound 10b effectively attenuates rat cerebral ischemia injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 45 publications
(42 reference statements)
1
28
0
Order By: Relevance
“…3 Several researchers have reported that anti-apoptosis and anti-inammation action can ameliorate the progress of I/R. 4 High mobility group box-1 (HMGB1) is generally known as a non-histone DNA binding protein, which is involved in the stabilization of DNA and the promotion of transcription. Recently, HMGB1 has been found to be passively released by necrotic cardiomyocytes in response to ischemia and it also acts as an early mediator of inammation following I/R injury.…”
Section: Introductionmentioning
confidence: 99%
“…3 Several researchers have reported that anti-apoptosis and anti-inammation action can ameliorate the progress of I/R. 4 High mobility group box-1 (HMGB1) is generally known as a non-histone DNA binding protein, which is involved in the stabilization of DNA and the promotion of transcription. Recently, HMGB1 has been found to be passively released by necrotic cardiomyocytes in response to ischemia and it also acts as an early mediator of inammation following I/R injury.…”
Section: Introductionmentioning
confidence: 99%
“…In a murine model of cerebral ischaemia-reperfusion, NBP decreased the intracerebral levels of TNF-α and intracellular adhesion molecule-1, thereby reducing damage to brain tissue (17). In a rotenone-induced PD mouse model, NBP decreased damage to dopaminergic neurons in the midbrain (18). In accordance with these findings, the results indicated that 30 days of treatment with NBP during the establishment of an LPS-induced model significantly attenuated LPS-induced mesencephalic microglial activation in the early stages, and decreased the loss of dopaminergic neurons in addition to α-synuclein deposition in the substantia nigra in the late stages.…”
Section: Discussionsupporting
confidence: 80%
“…In the present study, it was observed that NBP inhibited the activation of microglia and decreased α-synuclein deposition and the loss of dopaminergic neurons in the substantia nigra of LPS-induced PD mice. NBP, also termed butylphthalide (C 12 H 14 O 2 ; molecular mass, 190) is an active ingredient isolated from the oil of celery seeds with multiple pharmacological effects (16)(17)(18), though the mechanisms underlying these effects remain unknown. NBP is a national class I chemical drug with independent intellectual property rights in China.…”
Section: Discussionmentioning
confidence: 99%
“…The homogenate was then centrifuged at 4000 rpm/min for 10 min at 4 °C. SOD activity and levels of MDA and GSH were measured as described previously [ 34 , 35 ]. Data were calculated in reference to the protein concentration in each sample.…”
Section: Methodsmentioning
confidence: 99%